Analisis Pemilihan Smartphone Dikalangan Mahasiswa Generasi Z Kota Bandung Menggunakan Pendekatan AHP (Analytical Hierarchy Process) - Imanuel Christiawan Prasetyo; Nenden Septihani; Mutiara Handayani; Yani Iriani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The rapid growth of smartphone usage in Indonesia, particularly among Generation Z students in Bandung amid a 15.5% market expansion in 2024, underscores diverse preferences influenced by lifestyle and multitasking needs. This study aims to identify priority smartphone specifications using the Analytical Hierarchy Process (AHP). Employing a mixed-methods approach, it surveys a purposive sample of 30 Generation Z students via structured questionnaires and in-depth interviews. Instruments include pairwise comparison matrices analyzed in Microsoft Excel for priority weights and consistency ratios (CR ≤ 0.1). Results reveal camera as the top criterion (priority 0.47), with sub-criteria priorities: cashback (0.49), resolution (0.49), fast charging (0.44), large internal storage (0.48), and iPhone brand (0.39). These findings conclude that producers should prioritize camera enhancements and promotional incentives to align with Generation Z demands, informing targeted production strategies.